Opportunities and Challenges for Islamic Education in the Age of Technological Advancement - Fatoni, Mahfud Heru; Sukari, Sukari (Jurnal Paradigma, 2024)
As society transitions from the industrial revolution to the 5.0 era, rapid technological advancements require adaptability and resilience. This study explores the Opportunities and Challenges for Islamic Education in the Age of Technological Advancement, focusing on how Islamic education can address these changes. Utilizing a scoping review methodology, the research examines existing literature related to the challenges and opportunities in Islamic education amid technological growth and societal shifts. Key challenges identified include moral decline, the rise of non-educational media for children, misuse of social media, increased competition, the pressures of modernization and democratic values, the need to maintain past achievements while navigating crises, and the global competition that requires adaptation. Additionally, the fast pace of technological progress poses challenges in ensuring Islamic education remains relevant while promoting character development and Islamic values. To overcome these challenges, Islamic education can leverage opportunities such as enhancing religious understanding to develop both spiritual and emotional intelligence, creating and sharing content aligned with Islamic values through accessible media, prioritizing character education, and equipping students with 21st-century skills. Educators must also embrace innovation, adapt to modern tools responsibly, and ensure that technology is used in ways that uphold ethical principles. This balanced approach will prepare future generations to succeed in society 5.0 without compromising their core Islamic values.